Maternal intrapartum antibiotic administration and infantile colic : Is there a connection? - Leppälehto, Elli (My University, 2019)
Background: The etiology of infantile colic remains unknown. However, altered gut microbiota composition has been reported in children with the disorder. Objective: The objective of this study was to determine the associations between perinatal factors potentially affecting gut colonization and infantile colic. Methods: Altogether 48 infants with colic and 29 controls were selected from two ongoing clinical studies. Infants with and without colic were comparable with regard to their background characteristics. Results: A significant difference was detected in intrapartum antibiotic use and breastfeeding rates between infants with and without colic. The association between exposure to intrapartum antibiotics and infantile colic remained statistically significant after adjusting for potential confounding factors. Conclusions: Since intrapartum antibiotic exposure may have an effect on early gut colonization, our finding is consistent with the association between aberrant early gut microbiota composition and development of colic. Antibiotic-exposed neonates may represent a novel target group for preventive intervention studies.
Keywords: breastfeeding, infantile colic, intrapartum antibiotics, antibiootti, itku, koliikki, suolistomikrobisto